Psychiatric Neurotherapeutics Contemporary Surgical and Device-Based Treatments - Camprodon, Joan A.; Rauch, Scott L.; Greenberg, Benjamin D.; Dougherty, Darin D. (Current Clinical Psychiatry, 2016)
This volume covers the gamut of surgical and device-based treatments for psychiatric disorders. Written by experts in the field, this book covers neuroscience advances in the neurobiological underpinnings of psychiatric diseases, emerging surgical and device-based treatments, and advances in the field. Topics include electroconvulsive therapy, transcranial magnetic stimulation, Vagus nerve stimulation (VNS), and many other cutting-edge treatments and techniques. Psychiatric Neurotherapeutics is a valuable resource for psychiatrists, neurosurgeons, neurologists, researchers, and all other medical professionals interested in surgical and device-based treatments of psychiatric disorders.          .